2005
DOI: 10.1520/jfs2004423
|View full text |Cite
|
Sign up to set email alerts
|

A Duplex Real-Time qPCR Assay for the Quantification of Human Nuclear and Mitochondrial DNA in Forensic Samples: Implications for Quantifying DNA in Degraded Samples

Abstract: A duplex real-time qPCR assay was developed for quantifying human nuclear and mitochondrial DNA in forensic samples. The nuclear portion of the assay utilized amplification of a ∼170-190 bp target sequence that spans the repeat region of the TH01 STR locus, and the mitochondrial portion of the assay utilized amplification of a 69 bp target sequence in the ND1 region. Validation studies, performed on an ABI 7000 SDS instrument using TaqMan R detection, demonstrated that both portions of the duplex assay provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 36 publications
3
60
0
3
Order By: Relevance
“…This approach has been used by Alonso et al [6] who have developed two singleplex qPCR assays to separately quantify short and long mitochondrial target sequences to assess degradation in forensic samples. As part of our previous development and validation of a duplex qPCR assay for quantifying nuclear and mitochondrial DNA [7], we have also shown that for highly degraded samples the quantity of DNA depends significantly on the length of the target sequence that is amplified in the assay. For highly fragmented DNA samples, a qPCR assay that amplified a 62 bp target sequence detected more DNA than a qPCR assay that amplified a $170-190 bp target, a result consistent with the allele-length-dependent STR intensity profiles that are commonly seen for degraded DNA [8].…”
Section: Introductionmentioning
confidence: 92%
“…This approach has been used by Alonso et al [6] who have developed two singleplex qPCR assays to separately quantify short and long mitochondrial target sequences to assess degradation in forensic samples. As part of our previous development and validation of a duplex qPCR assay for quantifying nuclear and mitochondrial DNA [7], we have also shown that for highly degraded samples the quantity of DNA depends significantly on the length of the target sequence that is amplified in the assay. For highly fragmented DNA samples, a qPCR assay that amplified a 62 bp target sequence detected more DNA than a qPCR assay that amplified a $170-190 bp target, a result consistent with the allele-length-dependent STR intensity profiles that are commonly seen for degraded DNA [8].…”
Section: Introductionmentioning
confidence: 92%
“…To confirm the nuclear DNA content, all diluted samples were quantified again. To determine the corresponding mtDNA content, 800-900 mtDNA genome equivalents per cell [2,9,28], or rather 128±11 mtDNA genome equivalents per pg chromosomal DNA were calculated (personal communication: H. Niederstätter, GMI, Innsbruck, Austria).…”
Section: Samples Dna Extraction and Quantificationmentioning
confidence: 99%
“…Thus, the specimens pass through a chemical and physical ageing process which also causes a reduced survival rate in tardigrades after rehydration . For degraded template DNAs other pairs of primers for small amplicons or other methods for typing of degraded DNA should be used, which are common in the field of forensic research (Timken et al 2005;Meissner et al 2007).…”
Section: Discussionmentioning
confidence: 99%